Target space diffeomorphisms in Poisson sigma models and asymptotic symmetries in 2D dilaton gravities - Valcárcel, Carlos (Physical Review D)
The dilaton gravity models in two dimensions, including the Jackiw-Teitelboim model and its deformations, are particular cases of Poisson sigma models. Target space diffeomorphisms map one Poisson sigma model to another. We propose to use these diffeomorphisms to identify asymptotic conditions, boundary actions, and asymptotic symmetries in distinct dilaton gravity models. As an example, we use the asymptotic conditions in Jackiw-Teitelboim gravity to construct an asymptotic problem with Virasoro symmetry in a class of asymptotically Rindler models. We show that the method can be applied to a wide class of pairs of dilaton gravities and discuss possible generalizations.